Effect of microstructure evolution at the interphase boundary on the thermal ageing embrittlement of CF8M cast austenitic stainless steel. (August 2022) - Kong, Byeong Seo; Shin, Ji Ho; Jeong, Chaewon; Jang, Changheui; Kang, Sung-Sik
Abstract: Thermal ageing embrittlement of a cast austenitic stainless steel, CF8M with 25% of δ-ferrite, was evaluated using various mechanical tests such as micro-hardness, small punch, tensile, and fracture toughness (J-R) tests. To simulate long-term service at operating temperature in light water reactors (LWRs), CF8M was thermally aged at 400 °C up to 10, 000 h. After thermal ageing for 5000 h, phase separation into Fe-rich and Cr-rich phases by spinodal decomposition and G-phase precipitation were observed in δ-ferrite, resulting in significant hardening in δ-ferrite. As ageing duration increased to 10, 000 h, additional changes in microstructure and micro-hardness in δ-ferrite were not significant. On the other hand, fracture properties, such as fracture toughness and small punch (SP) energy showed further reduction with ageing time, which could be related to elemental segregation at the austenite/ferrite interphase boundary. After reversion heat treatment at 550 °C for 1 h, spinodal decomposition was mostly disappeared, but G-phase precipitate in δ-ferrite and elemental segregation at the austenite/ferrite interphase boundary were not recovered, which could be responsible for the incomplete recovery of mechanical properties. Highlights: Thermal ageing of CF8M with 25 vol % of δ-ferrite was evaluated at 400 °C. Spinodal decomposition and G-phase precipitation were almost saturated after 5000 h ageing. Micro-hardness and tensile properties showed near-saturation behavior after 5000 h ageing. Small punch and fracture toughness tests showed additional loss of fracture resistance at 10, 000 h ageing. Segregation and clustering were observed at interphase boundary at 10, 000 h ageing.